Concept validation of separations for thorium-based radionuclide generator systems for medical application - Schacherl, Bianca; Maurer, Kiara; Schäfer, Martin; Remde, Yvonne; Geyer, Frank; Fried, Annika; Happel, Steffen Alexander; Benešová-Schäfer, Martina (Frontiers in Nuclear Engineering, 2024)
Targeted alpha therapy (TαT) represents an emerging and cutting-edge treatment option for patients dealing with highly challenging metastatic cancer diseases. Critically, the limited supply of alpha particle-emitting radionuclides, so-called alpha in vivo nanogenerators, hampers wider utilization of TαT in the clinical setting. This could effectively be circumvented by alternate production routes including straightforward purification and reformulation strategies. Radionuclide generators offer an immense potential in this regard in case simple and robust elution strategies can be provided still adhering to the high radioisotopic, radionuclidic, and radiochemical purity criteria.In this study, a first step towards novel separation strategies providing additional sources of alpha in vivo nanogenerators for TαT was taken by experiments with various metal surrogates. With different systems, 232 Th/ nat Ba was used as a radionuclide generator analogue to 227 Th/ 223 Ra and 232 Th/ nat Ba/ nat La as a triplet analogue to 229 Th / 225 Ra/ 225 Ac. For the 232 Th/ nat Ba system, three selective resins (UTEVA, TEVA, DGA-N) were evaluated. Two perturbations of the best-performing resin were further evaluated using a larger diameter column and a week of equilibration time. For the 232 Th/ nat Ba/ nat La separation system, a combined column with two selective resins (TK200, TK101) was employed and evaluated. In conclusion, the obtained results pave the way towards the establishment and implementation of alternative separation strategies in the radioactive proof-of-concept validation in the near future. 1 𝐴𝑐 89 227 (𝛽 -) 𝑇ℎ (𝛼) 𝑅𝑎 88 223 90 227